2014
DOI: 10.1128/jvi.03270-13
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Domain of PA from Bat-Derived Influenza-Like Virus H17N10 Has Endonuclease Activity

Abstract: e Influenza imposes a great burden on society, not only in its seasonal appearance that affects both humans and domesticated animals but also through the constant threat of potential pandemics. Migratory birds are considered to be the reservoir hosts for influenza viruses, but other animals must also be considered. The recently identified influenza-like virus genome, from H17N10 in bats, was shown to be markedly different from genomes of other known influenza viruses, as both its surface glycoproteins hemagglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Moreover, the crystal structure of the heterotrimeric bat-derived H17N10 polymerase, comprising PB2, PB1 and PA subunits, reveals some canonical RNA polymerase motifs and domains (Pflug et al, 2014). Besides, we also showed that the N-terminal domain of PA (PAn) from H17N10 has a similar endonuclease activity to that from categorized influenza A viruses (Tefsen et al, 2013). Although we were unable to rescue viruses containing the PAn domain from H17N10 in a PR8 background in these studies, we investigated the possibility of rescuing functional genes or domains from H17N10 in the background of a categorized influenza A virus.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, the crystal structure of the heterotrimeric bat-derived H17N10 polymerase, comprising PB2, PB1 and PA subunits, reveals some canonical RNA polymerase motifs and domains (Pflug et al, 2014). Besides, we also showed that the N-terminal domain of PA (PAn) from H17N10 has a similar endonuclease activity to that from categorized influenza A viruses (Tefsen et al, 2013). Although we were unable to rescue viruses containing the PAn domain from H17N10 in a PR8 background in these studies, we investigated the possibility of rescuing functional genes or domains from H17N10 in the background of a categorized influenza A virus.…”
Section: Introductionmentioning
confidence: 77%
“…Our recent finding that PAn codes for an endonuclease with activities comparable to human and avian PAn molecules (Tefsen et al, 2013) stimulated us to address the fundamental question of whether functional genes or genetic domains from H17N10 could be rescued in the background of PR8.…”
Section: An H1n1 Hybrid Virus Can Be Rescued With Ns1 Gene From Bat-dmentioning
confidence: 99%
“…The resulted plasmids were then transformed into E. coli strain BL21 (DE3) for protein expression5051. Briefly, the bacteria were grown to an optical density of ~0.7 at 600 nm (OD600) in LB medium with 100 μg/ml ampicillin at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of Nter-PA has been solved in several crystal forms with (or without) various ligands[61,62,[73][74][75][76][77][78][79]. Two years after the first structure of the PA catalytic domain…”
mentioning
confidence: 99%